If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8xsq + -4x = 24 Solving 8qsx + -4x = 24 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '4x' to each side of the equation. 8qsx + -4x + 4x = 24 + 4x Combine like terms: -4x + 4x = 0 8qsx + 0 = 24 + 4x 8qsx = 24 + 4x Divide each side by '8sx'. q = 3s-1x-1 + 0.5s-1 Simplifying q = 3s-1x-1 + 0.5s-1 Reorder the terms: q = 0.5s-1 + 3s-1x-1
| 1.95y=y+10+1 | | 3x+3=x+85 | | x^2-13x=-22 | | 80+30t-5t^2=0 | | 122-6x=39x+17 | | 8x-14=2x+14 | | s=2nr | | (2x+9)(6x-7)=0 | | (4x-7)= | | (x^2)-6(x)-1=0 | | 9w^6+42w^5+24w^4= | | 24x-36x^2=0 | | 8(6x-7)=96x | | -1/4(12x+4)+1/7(49x+21) | | 8-7x=119-28x | | 2x+3=x+85 | | -x^2+17x-23=5x+9 | | x^4-4x^2-2=0 | | 1.16y=y+1+0.5 | | 50-7x=20x+20 | | 5x+4=28x+12 | | 1.16y=y+1+0.3 | | 1.2=2x/3+5.1 | | 1.16y=y+1+1 | | x/5+8=6 | | -x^2+2x+58=-x+4 | | x/5+12=-20 | | 5x/2=11+2x/3 | | 3x^2y-6xy^2= | | 6x+13=69-3x | | 1/3(5-3x)=5/6(x-2) | | x-39=79 |